Systematic analysis of molecules regulating nitric oxide (NO) metabolism and vascular endothelium condition - I. Yu. Torshin; A. G. Chuchalin; O. A. Gromova (Фармакоэкономика)
Background. Nitric monooxide (NO) is a signaling molecule that plays an important role in many physiological processes, including the regulation of vascular tone, neurotransmission, immunity, mitochondrial respiration, and skeletal muscle contractility. Certain molecules, which are micronutrients or active ingredients of a number of drugs, improve NO biosynthesis and secretion.Objective: systematization of information on the impact of various molecules on the modulation of NO levels in normal and pathological conditions.Material and methods. An array of all currently available publications on fundamental and clinical studies of the effects of various molecules on NO levels was studied. By the query “nitric oxide” in the PubMed/MEDLINE database of biomedical publications 198,480 articles were detected, and by the query “nitric oxide AND endothelium” 27,869 articles were found (with a peak in 2005). After loading this sample, a systematic analysis of these 27,869 publications was performed using topological and metric approaches.Results. As a result of systematic analysis at least 123 molecules were identified, that, in one way or another, modulate NO biosynthesis in the body. Molecules that improve NO metabolism can be conditionally divided into four groups: (1) macro- and micronutrients; (2) components of natural extracts; (3) medicines; (4) molecules that affect nitric oxide metabolism through the reparation of glycocalyx damage. Of the above variety of molecules that affect endothelium and NO biosynthesis, sulodexide stands out (by its effect on the endothelium and glycocalyx).Conclusion. The use of sulodexide (a mixture of glycosaminoglycans with a high degree of pharmaceutical standardization) is one of the promising areas of therapy for endothelial dysfunction through the regeneration of glycocalyx, which is accompanied by the restoration of NO biosynthesis.